Validation Analysis of Teacher Readiness Instruments in Implementing the School Literacy Movement (GLS) - Otang Kurniaman; Radini Radini; Eddy Noviana; Dede Permana; Ningrum Melihayatri; Beny Al Fajar; Zufriady Zufriady; Fadhila Rahman (Indonesian Journal of Innovation Science and Knowledge, 2026)
The School Literacy Movement (GLS) is a national priority program designed to strengthen literacy culture in primary and secondary education. The success of this program is greatly influenced by the readiness of teachers as the main facilitators. This study aims to develop and test the validity and reliability of an instrument that can measure the level of teacher readiness in implementing GLS. The study used a quantitative approach with a survey design and involved 200 elementary school teachers in Riau Province selected through a purposive sampling technique. The instrument was a questionnaire with 156 statements, arranged based on indicators covering aspects of literacy habits, literacy activity development, and literacy-based learning. Validity analysis was conducted through an item-total correlation test, while reliability was calculated using the Cronbach's Alpha coefficient. The results showed that of the 156 statements, 141 were declared valid with item-total correlation values ranging from 0.251 to 0.906, while the remaining 15 items did not meet the criteria. The overall reliability value of the instrument reached 0.91, which is categorized as very high. In detail, the validity test at the habituation stage revealed that indicators related to the provision of a literacy environment and reading habits obtained high scores, while several items regarding independent reading activities and writing assignments needed revision. At the development stage, the majority of items were declared valid, particularly the indicators for diverse reading activities, creative writing, and book discussions, although there were some weaknesses in aspects of institutional facilities and certain writing practices. Meanwhile, at the learning stage, all instrument items were declared valid with strong factor loading values. These findings confirm that the developed instrument is suitable for use as a measuring tool for teacher readiness in supporting GLS. Furthermore, the research results can be used as a reference in developing training programs, mentoring, and formulating more targeted school literacy policies. Thus, this instrument not only contributes to the evaluation of teacher readiness but can also support improving the quality of literacy implementation in elementary schools.